2010
DOI: 10.1002/elps.200900776
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the interaction between fibroblasts and tumor cells on a microfluidic co‐culture device

Abstract: Fibroblasts and tumor cells have been involved in the process of cancer development, progression and therapy. Here, we present a simple microfluidic device which enables to study the interaction between fibroblasts and tumor cells by indirect contact co-culture. The device is composed of multiple cell culture chambers which are connected by a parallel of cell migration regions, and it enables to realize different types of cells to communicate each other on the single device. In this work, human embryonic lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 27 publications
(35 reference statements)
2
60
0
Order By: Relevance
“…Homogeneous cells of HLF-HLF and A549-A549 were used as control groups. Compared to control groups, HLF co-cultured with A549 became non-uniform, getting more protrusions stretching out largely along the direction of A549, similar to the results reported by Qin (Ma et al, 2010). Protrusions, termed pseudopods, are specialized cellular structures containing an array of different proteins (Insall, 2010).…”
Section: Cell Morphology On the Co-culture Devicesupporting
confidence: 74%
See 1 more Smart Citation
“…Homogeneous cells of HLF-HLF and A549-A549 were used as control groups. Compared to control groups, HLF co-cultured with A549 became non-uniform, getting more protrusions stretching out largely along the direction of A549, similar to the results reported by Qin (Ma et al, 2010). Protrusions, termed pseudopods, are specialized cellular structures containing an array of different proteins (Insall, 2010).…”
Section: Cell Morphology On the Co-culture Devicesupporting
confidence: 74%
“…Some researchers have compared effect of normal fibroblasts with that of CAFs on tumor cells and demonstrated that the former inhibit cancer progression (Silzle et al, 2004, Kuperwasser et al, 2004. However, other researchers found out that normal fibroblasts could induce tumor growth (Hao et al, 2013, Tripathi et al, 2012, Ma et al, 2010 and quiescent fibroblasts can get activated and may be key regulators of paracrine signaling during cancer progress (Lorusso & Rugg, 2008). Therefore, it is necessary to understand the mechanism between normal fibroblasts and tumor for personalized targeted anticancer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in chemical analysis, biomedicine, food safety inspection, environmental or metabolite detection continue to stimulate the demand for information collection by using multiplex technologies in the manner of smaller sample consumption, shorter reaction time, higher sensitivity and lower cost [1][2][3][4]. Notably, microchip-based detectionanalysis system is considered as a promising candidate to reach this goal due to its distinct advantages such as low dosage, environmental friendliness, high safety and sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al designed a simple microfluidic device, allowing for the multiple types of cells co-culturing in the separated microchambers, with the soluble factors diffusion through the parallel cell migration regions. 54 This study reproduced the biological process of fibroblasts recruitment in the presence of the tumor cells and the activation of fibroblasts with a high expression of specific marker (a-SMA). Furthermore, the molecular mechanism underlying this activated process of fibroblasts was elucidated by Lee et al 55 It was found that this paracrine loop mediated the activated process could be inhibited with the addition of transforming growth factor beta 1 (TGF-b1) receptor/ALK5 inhibitor into the medium of fibroblasts, which might support the target of cancer therapy to prevent activated fibroblast ( Fig.…”
Section: Fibroblastsmentioning
confidence: 73%
“…52 Meanwhile, fibroblasts are continuously induced by the diffusive factors secreted by tumor cells, and thus can be activated with the specific expression of a-smooth muscle actin (a-SMA). 52,53 Several microfluidic devices have been developed to investigate the interaction between fibroblasts and tumor cells within microenvironment by using separated microstructure 54 or pneumatic microvalves control 55 based on microscale engineering technology. Qin et al designed a simple microfluidic device, allowing for the multiple types of cells co-culturing in the separated microchambers, with the soluble factors diffusion through the parallel cell migration regions.…”
Section: Fibroblastsmentioning
confidence: 99%